PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 031TANJUNG SARI KECAMATAN PUJUD - Tobing, Susylawaty Lumban; ', Lazim; Novianna, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This Research aim to to increase process the study and result of learning IPS of class of III SD Country 031 Foreland of Sari of school year 2015 / 2016. this Subjek Research is student of class of III SD Country 031 Gist;Sari Foreland with the student amount as much 38 people, consisted of by 21 men and 17 woman. This research represent the Research of Class Action ( PTK) with two cycle executed at month;moon of year April 2015. data of Research menunjukan that study process and result of learning to experience of the make-up of. This matter is provable at activity score learn and student of during study process experience of the make-up of. first Cycle I meeting of presentase activity learn is 70,00% with the good category and mount equal to 5,00% at second meeting become 75,00% with the good category. Hereinafter first cycle II meeting of percentage of teacher activity mount to become 80,00% with the good category very and at second meeting mount again equal to 10,00% so that become 90,00% with the good category very. Student activity of during study process also mount. At first cycle I meeting of percentage of student activity is 60,00% with the good category and at second meeting mount equal to 5,00% so that become 65,00% with the good category. first Cycle II meeting return to mount to become 75,00% with the category very goodness. Second meeting of presentase of student activity mount equal to 10,00% becoming 85,00% with the category very goodness. Result learn the student also experience of the make-up of. Elementary score to UH I do a good deed the make-up of result of equal to 24,68% with the complete student amount as much 26 people and which is not complete 12 people. Complete of klasikal UH I is 68,42% with the average value 75,79 above KKM. UH II also experience of the make-up of result learn from elementary score equal to 43,29% with the complete student amount 35 people and is not complete 3 people. Complete of klasikal UH II 92,11% with the average value 87,11. From above solution earn in concluding that through/ passing applying model the direct study hence can improve the result learn the IPS of student of class of III SD Country 031 Tanjung Sari of Subdistrict Pujud.Key Words : Direct Study, Process Study